2007
DOI: 10.1049/iet-nbt:20070022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a miniaturised drug delivery system with wireless power transfer and communication

Abstract: The development of an implantable system designed to deliver drug doses in a controlled manner over an extended time period is reported. Key performance parameters are the physical size, the power consumption and also the ability to perform wireless communications to enable the system to be externally controlled and interrogated. The system has been designed to facilitate wireless power transfer, which is very important for miniaturisation as it removes the need for a battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…Alternative materials for microfabrication processing schemes for microchips will be modified to optimize mass production (decreases cost) and to produce defect-free membranes (prevents drug leakage) (Santini et al, 2000b;Staples, 2010). In 2003, MicroCHIPS developed reservoir arrays where the metal membranes coating the reservoirs were opened by electrothermal mechanism that behaves similarly to an electrical fuse (Maloney et al, 2005) instead of electrochemically (Smith et al, 2007;Stevenson et al, 2012). The structure of this device is similar to the first controlled release microchip demonstrated experimentally by Santini and his colleagues in Nature (Maloney et al, 2005;Smith et al, 2007).…”
Section: Current Researches On Implantable Microchips For Drug Deliverymentioning
confidence: 99%
“…Alternative materials for microfabrication processing schemes for microchips will be modified to optimize mass production (decreases cost) and to produce defect-free membranes (prevents drug leakage) (Santini et al, 2000b;Staples, 2010). In 2003, MicroCHIPS developed reservoir arrays where the metal membranes coating the reservoirs were opened by electrothermal mechanism that behaves similarly to an electrical fuse (Maloney et al, 2005) instead of electrochemically (Smith et al, 2007;Stevenson et al, 2012). The structure of this device is similar to the first controlled release microchip demonstrated experimentally by Santini and his colleagues in Nature (Maloney et al, 2005;Smith et al, 2007).…”
Section: Current Researches On Implantable Microchips For Drug Deliverymentioning
confidence: 99%
“…Recently, several novel approaches have been used to power BioMEMS devices for biological applications. These approaches involve the use of thin film batteries as discussed by Nathan et al [31], wireless power transmission as proposed by Smith et al [49] and battery recharging through the drug refill port as reported by Evans et al [29]. Wireless power transmission has been demonstrated successfully and has a strong potential for powering implantable BioMEMS to increase operation time.…”
Section: Long Operation Timementioning
confidence: 99%
“…These include, but are not limited to, the use of ultrasound [8], light waves [9], magnetic fields [10] and radio waves below 100 MHz [11]. Complex systems have also been integrated into a drug delivery module consisting of a receiving inductor, control circuitry chip and a drug delivery chip [12]. Each of these methods has its pros and cons.…”
Section: Introductionmentioning
confidence: 99%